The Role of Cognitive Theory in Language Learning Acquisition - Zaynitdinovna, Turdijanova Zarina (International Journal on Orange Technologies, 2023)
In the Soviet era, fashion models and designers always followed fashion trends. They mainly used two different sources. The first was materials developed by the creative commission on fashion and clothing culture of fashion houses, and the second was local and foreign fashion magazines. The creative commission prepared new materials in the fashion direction every year. Because the models and designers did not understand the magazines published in a foreign language, they were translated. For example, "Fashion Folio" magazine, considered a foreign fashion magazine, was translated. Fashion houses had libraries, and these materials were available in these libraries.